Interpersonal relations of older preschool-age children who are in the institutional care - Kovalenko, Alla (Social Welfare: Interdisciplinary Approach, 2019)
The article presents the research on the characteristics of the interpersonal relationships of older preschool-age children who are under institutional care. It reveals the dependence of the emotional components of such children’s attitudes to significant people and themselves on their status in the group. Children being brought up out of family have problems with their relationships with adults and peers; they have some deviations in the most important psychological formations, which in the future may negatively affect their psychological well-being.
Keywords: : interpersonal relationships; older preschool age; children who are under institutional care; sociometric status; emotional components of relationships